Steroid Sparing Immunosuppression in Management of Cardiac Sarcoidosis: A Systematic Review - Golnaz Roshankar; Jia Yan Zhang; Dwip Parekh; Kristin Lyons; Debra Isaac; Robert J.H. Miller (Health Sciences Review, 2022)
ABSTRACT: Background: Cardiac sarcoidosis (CS) is frequently treated with corticosteroids. However, given the complications associated with chronic corticosteroid therapy, disease modifying anti-sarcoidosis drugs (DMASDs) are frequently prescribed. We conducted a systematic review to evaluate use of DMASDs in CS. Methods and Results: We conducted a systematic review of Cochrane Central Register of Controlled Trials, and Ovid (MEDLINE and EMBASE). We included randomized controlled trials, clinical trials, and cohort studies examining outcomes in patients with CS managed with DMASDs. Two authors independently used predetermined criteria to perform initial screening, full text screening, and risk of bias assessment. Due to heterogeneity in study design and outcomes we summarized the data without meta-analysis. Sixteen studies met our inclusion criteria. Fifteen papers were retrospective cohort studies and one was an open label comparative study. Studies had at least moderate risk of bias in all domains. The most commonly described DMASD was methotrexate (MTX). Most studies reported improvement or lack of disease progression with DMASDs. The most commonly reported side effects were infection and hepatotoxicity. Conclusion: Although DMASDs are frequently prescribed for CS, there is no high-quality evidence to support this practice. Multi-center randomized trials are warranted to evaluate the efficacy of different immunosuppression strategies.